HOW WERE VENDOBIONT BODIES PATTERNED? - Valentine J.W. (My University, 2001)
It is difficult to assign the animal-like body fossils of the late Neoproterozoic to crown metazoan phyla. Many Neoproterozoic fossils appear to share an architectural theme, which was characterized by Seilacher (1984, 1989) as modular; he noted that the modules, named pneus, could be arranged in a series of distinctive geometries to produce many of the Neoproterozoic fossil morphologies. The assemblages of pneus formed “quilted” constructions. Seilacher further suggested that these fossils might represent a multicellular clade that evolved independently of Metazoa—in effect, that they represented a kingdom of their own, which he named the Vendozoa. In later contributions, Seilacher (1992) renamed putatively quilted forms as the Vendobionta, and Buss and Seilacher (1994) considered Vendobionta to be a possible sister to Eumetazoa. The affinities suggested for vendobionts by various workers form a long list, ranging from protistans through fungi to several animal groups. Many vendobionts appear to be at the tissue grade of construction, and in this respect resemble cnidarians, to which they are most often compared. Neoproterozoic fossil assemblages also contain numbers of forms that are unlikely to be vendobionts, including a variety of “medusoids,” tentaculate fossils such as Hiemolora and Ediacaria (see Fedonkin 1992) that somewhat resemble sea anemones and may well be stem anthozoans. Additionally, numbers of Neoproterozoic forms have been suggested to be bilaterians, most notably the sluglike Kimberella (Fedonkin and Waggoner 1997). The contents and morphological limits of Vendobionta, and of some other higher taxa proposed for Neoproterozoic forms, are uncertain. Using molecular techniques, developmental biologists have clarified the basic genetic underpinnings of animal bodyplans (see Gilbert 1997; Wolpert et al. 1998; Carroll et al. 2001). Hox genes were among the earliest of the key developmental genes to be identified, first in Drosophila, and later in all eumetazoan phyla whose genomes have been …
Keywords: Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская